IMPROVING THE STUDENTS’ ABILITY IN WRITING NARRATIVE PARAGRAPH THROUGH FREE WRITING BLIND TYPING - Ilmiah, Ilmiah (Fakultas Keguruan dan Ilmu Pendidikan, 2015)
This research aims at  finding out the improvement the students’ ability in writing narrative paragraph through free writing( A Classroom Action Research in Class XI IPA 3 of Sma Negeri 1 Sinjai Barat, Sinjai) The researcher questions of the research are how do the students improve their writing proficiency in narrative paragraph by using free writing blind typing? and how do the students improve their writing proficiency in recount paragraph by using free writing blind typing? The researcher used A Classroom Action Research (C.A.R). Two cycles had been conducted, where each cycle consisted of four meetings. It employed writing test as instrument. A number of subjects of the research were 35 students of class XI IPA 3. The results of the student's writing test in cycle 1 and cycle 2 had increased in different scores.  There was increasing by students at the end action of second cycle. The means scores of narrative in data source was 61.90 become 68.33 in cycle 1, and after revision in the cycle 2 the mean score in cycle 2 was 76.66 by implemented of recount text. Therefore the improvement of narrative text in cycle 1 to recount text in cycle 2 was 23.84%. Meanwhile, the successful minimal criteria (KKM) was 65. The research findings indicated that use of Freewriting Blind Typing method could increase the students’ writing proficiency.